Robustness-Related Issues in Speaker Recognition - Zheng, Thomas Fang.; Li, Lantian; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book presents an overview of speaker recognition technologies with an emphasis on dealing with robustness issues. Firstly, the book gives an overview of speaker recognition, such as the basic system framework, categories under different criteria, performance evaluation and its development history. Secondly, with regard to robustness issues, the book presents three categories, including environment-related issues, speaker-related issues and application-oriented issues. For each category, the book describes the current hot topics, existing technologies, and potential research focuses in the future. The book is a useful reference book and self-learning guide for early researchers working in the field of robust speech recognition.
Speaker Recognition: Introduction -- Environmental-Related Robustness Issues -- Speaker-Related Robustness Issues -- Application-Oriented Robustness Issues -- Conclusions and Future Work.
Keywords: Signal processing; Pattern recognition systems; Computational linguistics; Signal, Speech and Image Processing; Automated Pattern Recognition; Computational Linguistics